UPAYA MENINGKATKAN KEPUASAN TAMU MELALUI KUALITAS PELAYANAN BARISTA DI GENTLE BEN KITCHEN AND COFFEE - Aldo Juwarno; Hurdawaty, Ramon (Jurnal Pendidikan dan Perhotelan (JPP), 2023)
Baristas as the front line have a significant influence on the success of a coffee shop. A barista must show his best service. However, some guests felt they were not cared for when they entered Gentle Ben Kitchen and Coffee by the barista. There is still a lack of basic understanding of the service of a barista in maintaining coffee shop operations. The purpose of this research is to find out the efforts to increase guest satisfaction through the quality of barista service at Gentle Ben Kitchen and Coffee. This research was conducted using qualitative methods through interviews and observations. The informant retrieval technique used in this study was purposive sampling. The results of this study are efforts to increase guest satisfaction through the quality of barista service at Gentle Ben Kitchen and Coffee that barista must work according to the SOP (Standard Operational Procedure) set by the company and must implement 3S (smile, greet, greet) to each customer to increase guest satisfaction. Steps that can be taken by the barista at Gentle Ben Kitchen and Coffee to increase guest satisfaction by being friendly, dressing politely and attractively, and training is needed before starting work.